2011
DOI: 10.1007/s00464-011-1617-1
|View full text |Cite
|
Sign up to set email alerts
|

Barrier methods used to prevent pelvic adhesions in videolaparoscopy: experimental study in female rabbits

Abstract: No difference was found using barrier methods, Surgicel(®), and Interceed(®) for preventing adhesion formation in videolaparoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…All the animals in the polypropylene group had omental adhesions, but also small intestine and colon. This finding is well described by many available studies 2 , 5 , 6 , 11 , 17 , 29 . The adhesions could be easily detached from the mesh in both groups.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…All the animals in the polypropylene group had omental adhesions, but also small intestine and colon. This finding is well described by many available studies 2 , 5 , 6 , 11 , 17 , 29 . The adhesions could be easily detached from the mesh in both groups.…”
Section: Discussionsupporting
confidence: 85%
“…What we can formulate is that absorption of the regenerated oxidized cellulose exposes the polypropylene layer to the abdominal visceral content and that this consequently led to the adhesions found. Another experimental study showed that regenerated oxidized cellulose caused adhesions in almost half of the animals in the study 2 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We combined two methods to achieve adhesion genesis as follows: the right horn was subjected to an incision and hereon sutured, whereas the left horn was abraded by friction. Other methods to create adhesion models have been described and include cecum abrasion [27], peritoneal lesion [28] and uterine lesion with bipolar electrocoagulation [29]. Nevertheless, these studies were conducted in small animals (rodents) and included a shorter postoperative period (up to 3 mo).…”
Section: Discussionmentioning
confidence: 98%
“…It is commonly assumed that both laparoscopic surgery and APM reduce SBO incidence. Three APMs (Seprafilm, 3,4 which comes in rolls and Interceed, 5,6 provided in sheets, and AdSpray, 7,8 which is a spray) are now available in Japan. However, there is no evidence that these APMs decrease SBO incidence.…”
Section: Introductionmentioning
confidence: 99%